(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The article offers an insight into the process of decryption and the content of the second, unpublished travelogue Seven Seas and Three Oceans by the Serbian writer Jelena J. Dimitrijević. The first part of the article is dedicated to the challenges and difficulties during the process of decrypting the manuscript of Jelena Dimitrijević. Six researchers from the project team Knjiženstvo have been working on this process. The second part consists of an overview analysis of the decrypted text with an accent on the key moments of the poetics and aesthetics of Jelena Dimitrijević’s writing. The main purpose of this article is to show the team results in the interpretation of a forgotten manuscript. Finally, the goal is to continue the affirmation of the rich opus of this Serbian writer and a world traveller, who in the last couple of years became the focus of many researchers, as well as the general public.